LEGAL FRAMEWORK GOVERNING THE AREA OF TRADE AND MARKETS IN THE REPUBLIC OF SERBIA WITH SPECIAL REFERENCE TO THE TRADE OF GOODS WITH THE AUTONOMOUS PROVINCE OF KOSOVO AND METOHIJA (Heritage, 2021)
Trade in modern market conditions has a complex and very important role in economic and social development. In Serbia, trade and market issues are gaining importance with the beginning of the approach toward the single European market. In parallel, the first modern strategic directions in the field of market development and trade policy have been created. Trade Development Strategies of the Republic of Serbia were the basis for the preparation and enactment of trade laws. The 2019 Trade Act in a modern and comprehensive way regulates the area of trade and markets in the Republic of Serbia. However, after its adoption, a timely and intensive implementation of the created resolutions is necessary. Also, a firm commitment is needed towards future amendments to this act, as it is a very dynamic area that requires close monitoring and a full understanding of the changes that are happening in the environment. Special attention should be focused on analysing the current situation, further developments and regulating the trade of goods with the Autonomous Province of Kosovo and Metohija.
Keywords: trade, market, trade policy, strategy, law, Autonomous Province of Kosovo i Metohija.